New method of language learning: Language awareness with adults - (:unkn) unknown (Slovenska Vzdelavacia Obstaravacia, 2014)
In today's world, to build a good career for individuals, good advice is: attempting to learn one or more foreign languages through new language learning methods. In this situation, teachers teach learners more languages by the aid of so called ‘singular’ and pluralistic approaches. In this vision, the article aims to demonstrate the application of a method of multi-faceted approach including ‘language awareness’ within the classroom practice. With this method, the motivation and willingness of learners increase. As part of our experience as a practitioner, I begin this work by a copy of the text "multilingual mouse" while learning FFL with students. Learners understand the mission of the same text written three times in Spanish, Italian and English. I continue this activity to discover the similarities and differences between these three languages. Finally, learners try to translate this text into French. I will develop this activity with the results of the xperiment, the views of learners and different aspects emerged from this empirical workshop in the entire text. © 2014, Slovenska Vzdelavacia Obstaravacia. All rights reserved.
Keywords: Adults; FFL; Language awareness